PERAN NEGARA DALAM PEMBERANTASAN KORUPSI DAN SANKSI PIDANA BAGI PELAKU - Edwin Yuliska (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Corruption is an act carried out with the intention of gaining profit that is against the law, corruption through misappropriation or misuse of state funds (companies, organizations, foundations, etc.) for personal gain or for other people, which is an evil and destructive act. . This research is entitled The State's Role in Eradicating Corruption and Criminal Sanctions for Perpetrators. The method used is a normative legal research type (normative juridical), namely normative legal research or library research. legislation, legal theory, and can be in the form of opinions of scholars. The discussion in this paper is, the definition of corruption, the role of the state in eradicating corruption, punishment for corruptors. Then the conclusion of this paper is corruption by enriching oneself by using power and using state money for personal gain. The causes include the absence and weakness of leaders, weaknesses in teaching and ethics, low education and poverty. There are harsh punishments, both criminal sanctions in the form of basic punishment and additional punishment for corruptors.Keywords: Corruption, Corruption Eradication, Corruptor Punishment.